Anywhere else but here - Clements, Bruce (Farrar, Straus, Giroux, 1980)
When her father's printing business goes broke, 13-year-old Molly wants to leave Schenectady, New York, and start over in Connecticut, but matters are complicated by two selfish, conniving people.